Single Incision Dual Cover with Temporoparietal Fascial Flap for Exposed Cochlear Implant: A Novel Take on a Workhorse Flap - Begum, U. Rasheedha; Kandasamy, Mahadevan; Christabel, Prethee Martina (Indian Journal of Plastic Surgery, 2024)
Cochlear implant surgeries have become increasingly common in India, leading to a rise in complications such as cochlear implant exposure. To address this issue, we present a novel technique involving a single incision dual cover using the temporoparietal fascial flap (TPFF) and skin flap to give durable cover for exposed cochlear implants.Materials and Methods A retrospective study was conducted between December 2019 and December 2022 on patients who underwent the dual flap procedure for exposed cochlear implants.Results The average defect size was 2 × 2 cm, and the average length of hospital stay was 10 days. Fourteen skin flaps were closed primarily, while two required skin grafting for donor site closure. At the time of discharge, all wounds showed successful healing with intact skin coverage over the cochlear implant device site. The average follow-up period was 12 months, during which two patients had donor site scar alopecia, while others had adequate hair growth masking the scar. All patients consistently used their cochlear implants.Conclusion Our single-incision, dual cover TPFF + skin flap technique offers a reliable and innovative solution for managing exposed cochlear implants. With successful implant salvage and favorable postoperative outcomes, this approach demonstrates the versatility and reliability of the TPFF as an excellent option for reconstructive surgeons dealing with cochlear implant complications.
Keywords: exposed cochlear implant; single incision; temporoparietal fascial flap; dual cover; cochlear implant salvage